CD147 Is a Promising Target of Tumor Progression and a Prognostic Biomarker - Landras, Alexandra (Cancers (Basel), 2019)
Microenvironment plays a crucial role in tumor development and progression. Cancer cells modulate the tumor microenvironment, which also contribute to resistance to therapy. Identifying biomarkers involved in tumorigenesis and cancer progression represents a great challenge for cancer diagnosis and therapeutic strategy development. CD147 is a glycoprotein involved in the regulation of the tumor microenvironment and cancer progression by several mechanisms—in particular, by the control of glycolysis and also by its well-known ability to induce proteinases leading to matrix degradation, tumor cell invasion, metastasis and angiogenesis. Accumulating evidence has demonstrated the role of CD147 expression in tumor progression and prognosis, suggesting it as a relevant tumor biomarker for cancer diagnosis and prognosis, as well as validating its potential as a promising therapeutic target in cancers.